2009
DOI: 10.1007/s11540-009-9140-7
|View full text |Cite
|
Sign up to set email alerts
|

Potato Transformation with Modified Nucleotide Sequences of the cry9Aa2 Gene Improves Resistance to Potato Tuber Moth

Abstract: The efficacy of four versions of a cry9Aa2 gene was evaluated against larvae of potato tuber moth (PTM; Phthorimaea operculella Zeller) following transfer to potato (Solanum tuberosum L.). A truncated native cry9Aa2 gene and three modified versions (G7, G10 and G14) were used, each with progressively more nucleotide substitutions to produce up to 79 codon changes to more closely resemble the codon bias of dicotyledonous plants. All four cry9Aa2 genes, under the transcriptional control of a CaMV 35S promoter, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 32 publications
(57 reference statements)
1
12
1
Order By: Relevance
“…4). However, this level of resistance was no greater than that previously observed from the use of only the cry1Ac9 gene (Davidson et al 2002, 2004, Meiyalaghan et al 2006a or only the cry9Aa2 gene (Meiyalaghan et al 2005(Meiyalaghan et al , 2006aJacobs et al 2009). The failure to observe an enhanced level of resistance to PTM larvae is surprising given the previous experimental results from simulating the pyramiding of several cry genes (Meiyalaghan et al 2006c).…”
Section: Re-transformation Simultaneous Transformationcontrasting
confidence: 54%
See 2 more Smart Citations
“…4). However, this level of resistance was no greater than that previously observed from the use of only the cry1Ac9 gene (Davidson et al 2002, 2004, Meiyalaghan et al 2006a or only the cry9Aa2 gene (Meiyalaghan et al 2005(Meiyalaghan et al , 2006aJacobs et al 2009). The failure to observe an enhanced level of resistance to PTM larvae is surprising given the previous experimental results from simulating the pyramiding of several cry genes (Meiyalaghan et al 2006c).…”
Section: Re-transformation Simultaneous Transformationcontrasting
confidence: 54%
“…Considerable variation in transgene expression among independently derived insect-resistant transgenic plants has been commonly reported in other studies (e.g. Peferoen et al 1990;Van Rie et al 1994;Beuning et al 2001), including Iwa potato lines transgenic for either the cry1Ac9 gene (Davidson et al 2002(Davidson et al , 2004Meiyalaghan et al 2006a) or the cry9Aa2 gene (Meiyalaghan et al 2005(Meiyalaghan et al , 2006aJacobs et al 2009). Such variation is usually attributed to unpredictable levels of transgene expression as a consequence of position effects resulting from differences Plant Biotechnol Rep (2010) 4:293-301 299 in the integration site of the transgenes within the plant genome and/or differences in T-DNA copy number (Conner and Christey 1994).…”
Section: Re-transformation Simultaneous Transformationsupporting
confidence: 52%
See 1 more Smart Citation
“…One of the main aspects to be considered in this regard are position effects, which are a result of the random integration of transgenes into a genome (Barrell et al, 2013). Position effects frequently are reported in potato and can override the regulatory control of the pro moter associated with the transgene, such that the tran script level, as well as the temporal and spatial expression patterns of the transgene are altered (Meiyalaghan et al, 2006;Barrell & Conner, 2009;Jacobs et al, 2009;Bar rell et a l, 2013). It has been shown that in A. thaliana methylation of the 35S promoter can cause epigenetic si lencing of transgenic RNAi constructs, leading to strongly varying levels of small RNAs between lines (Kyndt et al, 2013).…”
Section: Meloidogyne Chitwoodi Rnai Resistance In Potatomentioning
confidence: 99%
“…When developing large populations of independently derived transgenic lines, only the first shoot to regenerate from each transformation event is usually selected [14,17]. This is based on a widely held view that minimum time in tissue culture is favourable to avoid undesired somaclonal variation [32], and the assumption that a shoot taking a longer time to regenerate has a greater chance of producing off-types.…”
Section: Discussionmentioning
confidence: 99%